2019
DOI: 10.1021/acsmaterialslett.9b00371
|View full text |Cite
|
Sign up to set email alerts
|

Mesogens with Aggregation-Induced Emission Formed by Hydrogen Bonding

Abstract: In this contribution, we report a supramolecular approach toward mesogens showing aggregation-induced emission (AIE). AIE-active aromatic thioethers, acting as hydrogen-bond donors, were combined with alkoxystilbazoles as hydrogen-bond acceptors. Upon self-assembly, hydrogen-bonded complexes with monotropic liquid crystalline behavior were obtained. In addition, it was found that the introduction of a chiral citronellyl side chain leads to drastic bathochromic shift of the emission, which was not observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…Based on these results we were able to optimize our molecular design and reported recently a series of mesogens with aggregation‐induced emission formed by hydrogen bonding . The AIE behavior in the investigated hydrogen‐bonded materials was strongly dependent from their supramolecular structure and the resulting intermolecular packing.…”
Section: Supramolecular Liquid Crystalsmentioning
confidence: 79%
“…Based on these results we were able to optimize our molecular design and reported recently a series of mesogens with aggregation‐induced emission formed by hydrogen bonding . The AIE behavior in the investigated hydrogen‐bonded materials was strongly dependent from their supramolecular structure and the resulting intermolecular packing.…”
Section: Supramolecular Liquid Crystalsmentioning
confidence: 79%
“…Recently, our group has shown that self-assembly provides an efficient way to tune fluorescence behaviour of liquid crystalline materials [ 21 ]. Phenolic thioethers showing aggregation-induced emission properties were combined with alkoxystilbazoles to form hydrogen-bonded mesogens.…”
Section: Resultsmentioning
confidence: 99%
“…The Giese group reported a hydrogen‐bonded mesogens based on the AIE‐active luminophores introduced by Voskuhl and coworkers (e.g., ATE‐5 , Figure 29A). [ 70 ] Here, they mixed solutions of AIE‐active aromatic thioesters (hydrogen bond donor) with azopyridines and stilbazole derivatives (hydrogen bond acceptors) to yield a ratio of 1:2 (HB donor: HB acceptor). Upon slow evaporation of the solvent, a series of liquid crystalline assemblies was obtained showing a bathochromic shift compared to the starting materials (Figure 29A).…”
Section: Supramolecular Approachmentioning
confidence: 99%
“…In 2013, Yu et al synthesized a series of TPE-triphenylene oligomers (TPE-20 and 21) (Figure 29B) and investigated their F I G U R E 2 9 (A) Structures of the hydrogen donor with AIE properties (ATE-5) and the hydrogen acceptor (St*) as well as photographs of the emission of the single components as well as the formed 2:1 complex under UV-light irradiation. Adapted and reproduced with permission from the American Chemical Society, copyright 2019 [70]. (B) Molecular structures of the TPE-triphenylene mesogens TPE-20 in (Z) and (E) configuration and TPE-21.…”
mentioning
confidence: 99%